Սահմանադրաիրավական պատասխանատվության էությունը և կիրառման հիմնախնդիրները Հայաստանի Հանրապետությունում - Մերի Խաչատրյան (ՀՀ ԳԱԱ հրատ.)
Конституционно–правовая ответственность наиболее важная гарантия принципа разделения властей, для полного соблюдения Конституции и законов. Миссия конституционно–правовой ответственности заключается в том, чтобы органы всех ветвей власти четко осознали свою ответственность в государстве и перед обществом. This article is concerned with the constitutional and legal responsibility as the most important guarantee of the principle of Checks and Balances, aiming at upholding the Constitution and laws. Moreover, the basic issue of the constitutional and legal responsibility is to make the authorities be aware of their responsibilities toward the country and society.
Keywords: Law